2012
DOI: 10.3389/fnhum.2012.00299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biomechanical constraints in the hand laterality judgment task: where does it come from?

Abstract: Several studies have reported that, when subjects have to judge the laterality of rotated hand drawings, their judgment is automatically influenced by the biomechanical constraints of the upper limbs. The prominent account for this effect is that, in order to perform the task, subjects mentally rotate their upper limbs toward the position of the displayed stimulus in a way that is consistent with the biomechanical constraints underlying the actual movement. However, the effect of such biomechanical constraints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 45 publications
5
39
0
Order By: Relevance
“…Our findings thus considerably extend previous results obtained with IDs or congenital paralysis (19,(32)(33)(34)(35). It has been shown that individuals with congenital paralysis of facial muscles recognize facial expressions despite their inability to perform facial movements (32).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our findings thus considerably extend previous results obtained with IDs or congenital paralysis (19,(32)(33)(34)(35). It has been shown that individuals with congenital paralysis of facial muscles recognize facial expressions despite their inability to perform facial movements (32).…”
Section: Discussionsupporting
confidence: 73%
“…It has been shown that individuals with congenital paralysis of facial muscles recognize facial expressions despite their inability to perform facial movements (32). It also has been found that individuals with upper limb dysplasia are influenced by body biomechanical constraints when asked to judge the laterality of hand drawings (33)(34)(35). The present study goes well beyond the scope of this previous evidence by demonstrating that motor simulation contributes neither to the ease (speed) of action recognition nor to its robustness and does not contribute to the ability to anticipate others' movements perceptually, to predict the outcome of their actions, to read their mental states from their kinematics, or to memorize their body postures and movements.…”
Section: Discussionmentioning
confidence: 99%
“…In favor of the visual hypothesis, we (Vannuscorps & Caramazza, 2015) recently reported the case of one individual born with no upper limbs, P.M., whose response latency when asked to judge the laterality of a visually presented hand (Parsons, 1987) was influenced by the biomechanical complexity of the hand posture and position, as found for typically developed individuals. For instance, P.M. was slower at recognizing a right hand pointing to the right side of the screen than the same hand pointing to the left side, reflecting the smaller degree of freedom associated with lateral than medial hand movements.…”
Section: Introductionmentioning
confidence: 92%
“…However, the nature of the representations and processes underlying this perceptual bias remains unclear. According to a "visual hypothesis", the biomechanical bias in action perception reflects implicit knowledge ("internal model") of the body movement capabilities, accumulated in the course of perceptual learning and encoded in the visual system (Marr and Vaina, 1982;Tessari, Ottoboni, Symes, & Cubelli, 2010;Vannuscorps, Pillon, & Andres, 2012;Vannuscorps & Caramazza, 2015). According to a "motor hypothesis", this perceptual bias relies on the observer's own body somatosensory and motor representations, learned through movement execution (Knoblich, 2008;Thornton, Pinto & Shiffrar, 1998;Stevens et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Participant D.C. is a 53-year-old man whose performance in various experiments has already been reported (Vannuscorps, Pillon & Andres, 2012;Vannuscorps, Andres & Pillon, 2013, 2014. He has a master's degree in psychopedagogy.…”
Section: Methodsmentioning
confidence: 99%